Performance, carcass and meat traits of beef steers finished on small-grain winter annuals in winter or on alfalfa pasture in summer - Pordomingo, Anibal Javier; Pordomingo, Adriana Beatriz; Grigioni, Gabriela Maria; Carduza, Fernando Jose (Elsevier, 2021)
Performance and carcass traits of beef steers finished on small-grain winter annual pastures (SGWA) or alfalfa were compared. Treatments consisted of pure stands of cereal rye, triticale, wheat or alfalfa (Rye, Trit, Wht, and Alf, respectively). The 3 SGWA species were grazed during winter and early spring. Alfalfa was grazed during spring and summer. Three pasture replicates were assigned to each treatment with 10 animals each. A minimum of 7-mm subcutaneous rib fat thickness (determined by ultrasound) was defined as slaughter endpoint. After a 98-d finishing period all animals from Rye, Trit and Wht reached the target, and were ready for harvest. Alfalfa animals were slaughtered after 120 days. After slaughter, carcasses were individually graded and weighed to determine hot carcass weight (HCW) and hot carcass yield (HCY) was calculated. Seventy-two h post-slaughter, a section of steaks including the longissimus thoracis muscle (LT) was removed from the left side of each carcass for analysis including rib fat thickness (RFT), LT area (LTA), Warner-Bratzler-shear force (WBsf), drip-loss, cooking loss, instrumental color, muscle pH, sensory analysis, intramuscular fat content and lipid profile. Proximate composition, and lipid profiles of pastures offered were also determined. Alf animals had lower (P < 0.01) ADG than SGWA animals. Alfalfa animals took 22 days longer to reach the slaughter point. However, no pasture effects were detected (P ≥ 0.14) for HCY, LTA, RFT, WBsf, pH, muscle a* and b*, and subcutaneous fat L*, a* and b* color parameters. Muscle L* was greater (P < 0.05) and drip and cooking loss were lower (P ≤ 0.05) for Alf. Sensory panel scored Alf beef of greater (P < 0.01) juiciness, tenderness and beef-flavor. Rye beef was attributed highest off-flavor score. Alfalfa and Wht beef showed similar (P = 0.40) FA content, higher (P ≤ 0.02) than Rye and Trit beef. Rye beef had the lowest (P ≤ 0.02) FA content. Within the FA fraction, Alf had lower (P ≤ 0.02) proportion of SFA, greater t-MUFA content, greater (P ≤ 0.01) total n-3 concentration and the lowest n-6/n-3 ratio (P ≤ 0.01). Alfalfa beef resulted in greater (P ≤ 0.01) total CLA concentration. Although lipid profiles of forages related to observations in lipid profiles of beef, differences in drip and cooking loss and sensory attributes of beef that favored of alfalfa finishing were not explained in animal performance and fatness.